Pengaruh Terapi Murottal Q.S Ar Rahman Terhadap Status Hemodinamika Pada Pasien Hemodialisa - Rahmawati Dian Nurani (Citra Delima Scientific journal of Citra Internasional Institute, 2022)
Chronic kidney disease (CKD) is an irreversible and progressive damage to renal function in which the body's capabilities fail to carry out metabolic defenses. Hemodialysis is one of several treatments that can be done, but many sufferers face medical complications. Problems that are always experienced are hypertension and hypotension. One of several methods to improve hemodynamic status is Al-Qur'an murottal therapy. The purpose of this study was to determine the effect of murottal Al-Qur'an therapy on hemodynamic status. This research is a Quasy-Experiment using pre and post test with control group design. The sample of this research is 38 respondents using simple random sampling technique. The analysis used is the T test. The results showed that there was a decrease in systolic blood pressure (p value 0.000) and MAP (p value 0.000), HR (p value 0.017) and RR (p value 0.011) and there was no decrease in diastolic blood pressure (p value 0.112). The conclusion of this research is that murottal Al Qur'an performed for one week has an effect on decreasing hemodynamic status (systolic blood pressure, mean arterial pressure (MAP), heart rate (HR) and respiratory rate (RR) for hemodialysis patients.